Genome mining of WOX-ARF gene linkage in Machilus pauhoi underpinned cambial activity associated with IAA induction - Shen, Mingli; Zhao, Kai; Luo, Xianmei; Guo, Lingling; Ma, Zhirui; Wen, Lei; Lin, Siqing; Lin, Yingxuan; Sun, Hongyan; Ahmad, Sagheer (Frontiers in Plant Science, 2024)
As an upright tree with multifunctional economic application, Machilus pauhoi is an excellent choice in modern forestry from Lauraceae. The growth characteristics is of great significance for its molecular breeding and improvement. However, there still lack the information of WUSCHEL-related homeobox (WOX) and Auxin response factor (ARF) gene family, which were reported as specific transcription factors in plant growth as well as auxin signaling. Here, a total of sixteen MpWOX and twenty-one MpARF genes were identified from the genome of M. pauhoi. Though member of WOX conserved in the Lauraceae, MpWOX and MpARF genes were unevenly distributed on 12 chromosomes as a result of region duplication. These genes presented 45 and 142 miRNA editing sites, respectively, reflecting a potential post-transcriptional restrain. Overall, MpWOX4, MpWOX13a, MpWOX13b, MpARF6b, MpARF6c, and MpARF19a were highly co-expressed in the vascular cambium, forming a working mode as WOX-ARF complex. MpWOXs contains typical AuxRR-core and TGA-element cis-acting regulatory elements in this auxin signaling linkage. In addition, under IAA and NPA treatments, MpARF2a and MpWOX1a was highly sensitive to IAA response, showing significant changes after 6 hours of treatment. And MpWOX1a was significantly inhibited by NPA treatment. Through all these solid analysis, our findings provide a genetic foundation to growth mechanism analysis and further molecular designing breeding in Machilus pauhoi.